Heart rate and activity measured during volleyball competition using wearable technology - Gielen, J.; Mehuys, E.; Eyckmans, K.; Aerts, J.-M. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
Volleyball is characterised by intervals of high-intensity gameplay mixed with periods of relative rest. Monitoring the athletes` physiology during competition allows us to study the changes in exercise intensity throughout a game. In this study, eight elite male volleyball athletes measured their heart rate and activity during multiple games of the regular season in the Belgian Liga A and B using wearable technology. The data show a significant decrease in the heart rate for set 1 to 4, from 79.1 %HRmax to 73.9 %HRmax. For activity, a decreasing trend is visually observed, but the difference is only significant for set 1 compared to the other sets. Finally, the performance did not vary significantly over the course of the different sets.